Occurrence and Antibiotic Susceptibility Among Coliform Bacteria Isolated From Sewage Exposed Fish. - Samir Banerjee, Sutapa Sanyal, Abhisek Basu (Recent Research in Science and Technology, 2010)
Bacteriological contamination of muscles and digestive tract contents of Oreochromis sp. and Labeo sp. reared in a pond supplied with domestic sewage was enumerated followed by determination of resistance of thermotolerent coliforms for antibiotics. Numbers of bacteria in muscles and digestive tract contents of fish reflected their densities in water. Muscles of both the fish species contained high numbers of total coliforms (TC) and fecal coliforms (FC). Escherichia Coli (E. coli) were never recovered from the muscles but from the digestive tract contents of the fish. Ranking of the total and fecal coliform contamination levels showed a decrease in the order digestive tract contents> muscles (p<.05). The random thermotolerent coliform isolates from these fish organs showed resistance in decreasing order for tetracycline (82%) and ampicillin (65%). 58.11% (68 isolates out of 117) of the total isolates were resistant to both ampicillin and tetracycline. This observation indicates significant occurrence of bacterial population in organs of sewage fed fish with high incidence of antibiotic resistance which may pose risk to fish fauna and public health.